Hydrocarbon exploration by optimal cross spread techniques, and permit problems in Nigeria, semblances in Sudan, Ethiopia - C.L. Osanebi; A.J.C. Madu (Journal of Applied Sciences and Environmental Management, 2019)
One sure method for hydrocarbon exploration is the use of orthogonal geometries, in cross spread techniques. The configuration is based on consistent orthogonal pattern of both receiver lines and source lines. In areas where infrastructural facilities abound and interfere with seismic lines as obstacles, suitable designs of offsets, laminar or lateral types are employed to bypass the obstacles. The angle of excursion of the skirting from the main seismic line should be between17° and 34°. Around the intersection of lines with obstacles a skirting designed about the structure will maintain the source or receiver line spacing in multiples of the original line spacing. Densification of sources are used to recover the near-offset shots and near-mid offsets shots to upgrade the subsurface coverage that will compensate for the gap created by the omission of the obstacles. Compensation source line offsets, are designed as “skirting” around obstacles. This may result in drop in multiplicity or “fold of coverage “due to loss of Nears- and Near-mid CDP bins. Permit problems from host communities to the recording data acquisition is notable in this technique. The severity of the challenges partly varies with the extent of negative impact to the host communities or environment. Certain exploration activities adversely impact on the host communities and their sources of livelihood. The situation was different and in Ethiopia some years ago due to stiff opposition of the Ogaden basin youths in the coastal Somalian Region to Ethiopian Federal Government efforts on hydrocarbon exploration and development.